170 Operative Management of Adult Spinal Deformity Results in Significant Increases in QALYs Gained Compared With Nonoperative Management: Analysis of 479 Patients With Minimum 2-Year Follow-up. (August 2015) - Scheer, Justin K.; Hostin, Richard A.; Schwab, Frank; Robinson, Chessie; Lafage, Virginie; Burton, Douglas C.; Hart, Robert; Kelly, Michael P.; Keefe, Malla; Polly, David W.; Bess, Shay; Shaffrey, Christopher I.; et al.
Abstract : INTRODUCTION: Operative management of adult spinal deformity (ASD) repeatedly demonstrates improvements in health-related quality of life over nonoperative treatment. However, little is reported regarding the quality-adjusted life-year (QALY) improvements following surgical correction of ASD. The purpose of this study was to evaluate the QALY increases following the operative treatment of ASD compared with nonoperative treatment. METHODS: Inclusion criteria: =18 years, ASD. Health utility values were calculated from SF-6D scores and used to calculate QALYs gained or lost at a minimum 2 years from the baseline utility value. A subanalysis was conducted on the available patients in the cohort with complete 1-, 2-, and 3-year SF-36 scores to establish a trend in QALY changes. RESULTS: Three hundred sixty-five operative (OP) and 469 nonoperative (NONOP) patients were eligible for 2-year follow-up, and 479 patients were included (OP: 258 (70.7%), NONOP: 221 (47.1%). OP had significantly worse health utility values (0.545 ± 0.118 vs 0.657 ± 0.114, P < .0001), and larger QALY gained (0.139 ± 0.253 vs −0.004 ± 0.209, P < .0001). OP had lower QALY at minimum 2 years (1.28 ± 0.330 vs 1.39 ± 0.374, P = .0014). One hundred seventy-nine patients (OP: 106, NONOP: 73) had complete 1-, 2-, and 3-year SF-36 scores and were included in the subanalysis. Of these patients, both groups had statistically similar mean QALYs at all time points (OP vs NONOP, P > .05): 1 year (0.648 ± 0.102 vs 0.645 ± 0.090), 2 year (1.32 ± 0.232 vs 1.27 ± 0.204), and 3 year (1.97 ± 0.379 vs 1.93 ± 0.303). OP patients had a significantly larger increase in QALYs (from baseline) at 1, 2, and 3 years compared with NONOP (Figure): 1 year (0.084 ± 0.113 vs 0.011 ± 0.086, P < .0001), 2 year (0.179 ± 0.240 vs 0.005 ± 0.186, P < .0001), and 3 year (0.258 ± 0.354 vs 0.020 ± 0.258, P < .0001). CONCLUSION: The operative treatment of ASD results in significant increases in QALYs gained at minimum 2 years postoperatively as well as at the 1-, 2-, and 3-year time points compared with nonoperative management.